Being a scientist during covid-19 pandemic: does guided inquiry affect students’ creative thinking skills? - Linda Tri Antika; Atikutul Mukarromah (STKIP Persada Khatulistiwa Sintang, 2021)
Guided inquiry learning encourages students to be more active in learning so that students' creative thinking skills can be developed. Guided inquiry learning model will assist students in empowering creative thinking skills. Creative thinking skills are described as mental activities that foster original ideas and new understandings. This study aimed to determine the effect of the guided inquiry learning model on the creative thinking skills of Class X MA Miftahul Ulum Bettet Pamekasan. The population in the study were all students of class X MA Miftahul Ulum Bettet Pamekasan second semester 2020/2021, while the samples used were class X IPA B and IPA C. The experimental class and control class each consisted of 20 students. This research is a quantitative research with quasi-experimental research method with pretest posttest nonequivalent pretest-posttest control group design. The results of this study indicated that guided inquiry has a significant effect on creative thinking skills. Guided inquiry learning model can be a reference in learning (especially in biology) to empower students' thinking skills.